ANALISIS JARINGAN DAN PEMELIHARAAN PADA JARINGAN DISTRIBUSI DI PT.PLN WILAYAH CABANG PINRANG - Rizal Duyo; Andi Sulkifli (Fakultas Teknik Universitas Muhammadiyah Makassar, 2019)
Abstract— Used in electrical energy distribution effort to the community. Know the factors that affect the capacity of power distribution transformers for 3 phase and 1 phase and to know system maintenance performed on the distribution network and transformer at. PLN ( Persero ) Branch Pinrang .All data that is required in this study was obtained through several instruments such as surveys or direct observation , interviews , and a review of literature used to complement and meet the required data. All data were collected and analyzed using descriptive analysis . These results prove that the distribution network is used on the PT . PLN ( Persero ) Branch Pinrang consists of a primary distribution channels , distribution transformers and secondary distribution channels. This distribution network is used to distribute electrical energy to the entire community of Pinrang. Kapasitas of a distribution transformer for 3 phases and the first phase is determined by the amount of load that is served is added to the burden of the future development. System maintenance is performed on the distribution network and transformer at. PLN ( Persero ) Branch Pinrang done regularly and proactively with emphasis on preventive measures aiming to prevent disturbance of the action reprensif in overcoming the disorder.